Escalas representadas em gráficos: Um estudo de intervenção com alunos do 5º ano - Maria Betânia Evangelista; Gilda Lisbôa Guimarães (Universidade do Minho, 2015)
This article presents a study that investigated learning about scales represented in bar and line graphs after a teaching intervention. 69 students of the 5th grade (about 10 years old) of three Brazilian public schools participated in this study. For each group, activities involving different situations were proposed: length measure, number line and maps. All students participated in a pre-test, a teaching intervention and a post-test. The results revealed that students have difficulties to represent, locate, analyze, compare and build scales on graphs. However, after only two intervention sessions in each group, significant improvements were observed in the learning of all groups. Thus, we can say that students in primary school, when involved in thinking about scales, are able to learn about that representation. In that way, the need and possibility of a systematic work in schools is evidenced.